The Impacts of Integrating Real World Employer-Relations Project in the Classroom Activities and Assessments: A Case Study - Intan Syafinaz, Mohmad Rozee; Nadia Athirah, Jamaludin (INTI International University, 2019)
Nowadays, the industry expects graduates to be skilled from problem solving initiative to entrepreneurial skills, soft skills to communication and critical thinking to innovative mindset. These expectations have necessitated higher learning institutions to revisit the curriculum; thus redesigning teaching and learning processes to enhance graduates’ employability (MOE, 2015, 2017). To achieve the goals, an employer-relations project is conducted to determine as to whether employability skills can be enhanced through classroom activities and by tying up the course assessments with the “employer’s” expectations. This study uses mixed method to collect the evidences: journal entries, questionnaires and focus group discussion. The results show that the employer project helps to promote employability skills, in which the implication holds useful pedagogical impacts to teaching and learning in higher education.